KOMPETENSI PELAKU INDUSTRI KECIL DAN MENENGAH DALAM KONTEKS SMART ECONOMY: ANALISIS KAPASITAS OPERASIONAL, ADOPSI TEKNOLOGI, DAN KONEKTIVITAS BISNIS DI KOTA MATARAM, INDONESIA - Mutiara Mita Kasia; Idiatul Fitri Danasari; Sri Maryati; Ni Made Wirastika Sari; Iga Nabila Ouwan Azzahra (JURNAL AGRIMANSION, 2025)
In the Province of West Nusa Tenggara, Micro, Small, and Medium Enterprises (MSMEs) in the manufacturing sector contribute 3.76 percent to the Regional Gross Domestic Product (RGDP) and absorb 10.11 percent of the workforce. Their strategic role as a foundation of local and national economic activity highlights the need to strengthen their capacity, particularly amid ongoing digital transformation. This study analyzes the competency levels of Small and Medium Industry (SMI) actors in Mataram City in the context of the smart economy, which requires adequate capabilities in technology adoption, operational (entrepreneurial) capacity, and business connectivity. A mixed-method approach with a convergent parallel design was employed, involving 43 SMI respondents. The research instrument consisted of four constructs: Technology & Innovation Adoption (3 items, α=0.671), Operational Capacity (3 items, α=0.434), Product Image (1 item), and Business Connectivity (3 items, α=0.706). The findings show that most SMI actors are women of productive age, hold undergraduate degrees, operate small-scale businesses, and rely on personal capital, with monthly capital and turnover generally below IDR 50 million. Results indicate that 93.0% of SMIs exhibit high technological adoption (M=3.71), 72.1% demonstrate adequate operational capacity (M=3.15), and all respondents report positive product image (M=3.98). However, only 11.6% achieve high business connectivity (M=2.10), making it the weakest dimension. Correlation analysis reveals significant relationships between Operational Capacity and Business Connectivity (r=0.489, p<0.001), and between Technology Adoption and Business Connectivity (r=0.373, p<0.05). Senior entrepreneurs (>45 years) display the highest business connectivity, while younger entrepreneurs (26–35 years) lead in technology adoption. Policy recommendations emphasize enhancing digital connectivity, building collaborative ecosystems, and utilizing senior entrepreneurs as mentors.